2021
DOI: 10.1080/22221751.2020.1870412
|View full text |Cite
|
Sign up to set email alerts
|

A host-based whole genome sequencing study reveals novel risk loci associated with severity of influenza A(H1N1)pdm09 infection

Abstract: Influenza A(H1N1)pdm09 virus has remained in a seasonal circulation since being recognized in 2009. Although it followed a mild course in most patients, in others it caused a series of severe clinical illnesses. Epidemiologic studies have implicated that host factors have a major influence on the disease severity of influenza A(H1N1)pdm09 infection. However, an understanding of relevant genetic variations and the underlying mechanisms is still limited. In this present study, we used a host-based whole genome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The statistical models were adjusted for covariates including age, sex, the top 10 principal components (PCs), and trait‐specific covariates. In a previous study, we outlined the specific workflow to construct the GWAS for the severity of H1N1pdm09 disease 12 . In brief, we collected samples from 165 patients infected with H1N1pdm09.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical models were adjusted for covariates including age, sex, the top 10 principal components (PCs), and trait‐specific covariates. In a previous study, we outlined the specific workflow to construct the GWAS for the severity of H1N1pdm09 disease 12 . In brief, we collected samples from 165 patients infected with H1N1pdm09.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we employed a two‐sample MR analysis to investigate the causal relationship between human blood traits and the severity of H1N1pdm09 disease. We integrated our in‐house GWAS data on H1N1pdm09 disease severity 12 with the comprehensive GWAS summary of 44 blood traits from Biobank Japan (BBJ) 13 . This analysis allowed us to estimate the putative causal relationships between these traits and disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Real-time reverse transcription polymerase chain reaction (RT-PCR) was used for diagnosing H7N9 infection, following the Diagnostic and Treatment Protocol for Human Infection with Avian Influenza A (H7N9) (http://www.nhc.gov.cn/gjhzs/s7952/201304/34750c7e6 930463aac789b3e2156632f.shtml accessed on 30 May 2018). Similarly, summary statistics for H1N1 severity were collected from another preceding GWAS involving 165 Chinese H1N1pdm09 patients, confirmed by positive results of real-time RT-PCR [24]. Patients with mild symptoms (n = 95) were defined as outpatients not admitted to hospitals, while those with severe symptoms (n = 70) were hospitalized patients meeting specific criteria outlined in the Protocol for diagnosis and treatment of influenza (2019 version) [25].…”
Section: H7n9 Susceptibility and H1n1 Severity Gwas Datamentioning
confidence: 99%
“…Notably, multiple studies have shown that the expression of HIF-1α can also be upregulated under normoxic conditions ( Koyasu et al., 2018 ). A host-based whole-genome sequencing study identified the potential involvement of the HIF-1 transcription factor and the IFN-γ pathway in the pathogenesis of severe influenza A (H1N1) infection ( Li et al., 2021 ). H1N1 infection can cause lung and intestinal injury and imbalance of the intestinal flora.…”
Section: Introductionmentioning
confidence: 99%